Figure 17 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD, Bennett BA, Ponomarenko S (2020) Vascular plants of Victoria Island (Northwest Territories and Nunavut, Canada): a specimen-based study of an Arctic flora. PhytoKeys 141: 1-330. https://doi.org/10.3897/phytokeys.141.48810 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D.; Bennett, Bruce A.; Ponomarenko, Serguei (Zenodo, 2022)
Figure 17 ACarex rariflora habit BCarex rupestris habit CCarex rupestris habitat DCarex saxatilis habit. Photos by B.A. Bennett.